Pterostilbene nanoparticles with small particle size show excellent anti-breast cancer activity in vitro and in vivo. (19th May 2021) - Zou, Yuan; Wang, Xiangtao; Bi, Dongdong; Fu, Jingxin; Han, Jianwei; Guo, Yifei; Feng, Li; Han, Meihua
Abstract: Pterostilbene (PTE) is known as resveratrol of the next generation and it has attracted extensive attention in recent years. PTE can inhibit the growth of a variety of tumor cells. To overcome the problem of insolubility, PTE was loaded into nanoparticles (NPs) by anti-solvent precipitation technique using soybean lecithin (SPC) and D-α-tocopheryl polyethylene glycol succinate (TPGS) as stabilizers. The obtained PTE-NPs had an average particle size of 71.0 nm, a polydispersity index （PDI） value of 0.258, and a high zeta potential of −40.8 mV. PTE-NPs can maintain particle size stability in various physiological media. The entrapment efficiency of PTE-NPs was 98.24%. And the apparently water solubility of PTE-NPs was about 53 times higher than the solubility of PTE (54.41 μ g ml −1 v −1 s −1 . 2.89 mg ml −1 ). M −1 T −1 T −1 assay showed that the antitumor activity of PTE-NPs on 4T1 breast cancer cells, MCF-7 breast cancer cells and Hela cervical cancer cells was significantly increased by 4, 6 and 8 times than that of free PTE, respectively. In vivo studies have shown that PTE-NPs has a certain dose dependence. When injected intraperitoneally, PTE-NPs showed a similar therapeutic effect as paclitaxel injection (TIR was 57.53% versus 57.23%) against 4T1 tumor-bearing mice. This should be due to the improved bioavailability of the drug caused by nano-drug delivery system (nano-DDS). These results indicate that PTE-NPs may be a clinically promising anti-tumor drug for breast cancer treatment.